Giant left main coronary artery aneurysm: Srpski - Andjelković, Kristina; Drašković, Danijela; Kočica, Mladen; Radovanović, Jovana; Ivanović, Branislava (Vojnosanitetski pregled, 2023)
Introduction. Coronary artery aneurysms (CAAs) are rare disorders, especially the left main CAA. In the literature, there are several reported cases with CAAs, various localization, size, clinical presentation, and way of treatment. There is no unique consensus about the most adequate treatment for these patients; however, surgery is still preferable, although there are some new experiences of percutaneous treatment. The decision is made for each patient individually. We report a case of giant left main CAA, with acute coronary syndrome and heart failure presentation, surgically treated. Case report. A 66-year-old female patient was admitted to the emergency department of our clinic due to chest pain and dyspnea. Acute non-ST-elevation segment myocardial infarction (STEMI) of anterolateral localization was diagnosed (creatine kinase max 1,111 U/L, troponin T 3.754 ng/mL), complicated with acute heart failure. Heart catheterization and coronary angiography revealed a giant saccular, 3.5 × 3.5 mm left main CAA full with thrombi, compressing the proximal segments of the left anterior descending and circumflex artery. Conclusion. Giant left main CAAs are rare pathologic findings, and there are no established principles for treatment. Although the percutaneous way of treatment is now available in selected cases, the surgical approach is still preferred for these patients.
Keywords: cardiac catheterization; coronary aneurysm; coronary angiography; cardiac surgical procedures; diagnosis; non-st elevated myocardial infarction